Extranodal marginal zone lymphoma of mucosa‐associated lymphoid tissue of the salivary glands: A population‐based study from 1994 to 2009. Issue 1 (15th April 2014) - Vazquez, Alejandro; Khan, Mohemmed N.; Sanghvi, Saurin; Patel, Neal R.; Caputo, Joseph L.; Baredes, Soly; Eloy, Jean Anderson
ABSTRACT Background Extranodal marginal zone lymphoma of mucosa‐associated lymphoid tissue (MALT lymphoma) arising from the salivary glands is rare. Methods Five hundred seven cases were available for frequency/incidence analysis, and 712 for relative survival and regression analysis in the Surveillance Epidemiology and End Results (SEER) database. Results Of the total patients, 72.98% were women, 80.47% were white, and 74.75% were ≥50 years old. The parotid gland was involved in 80.87% of cases. Ann Arbor stage at diagnosis was 53.85% IE, 18.54% IIE, and 10.06% IIIE/IV. Overall, 15‐year relative survival was 78.40%. Relative survival was worst among blacks and those with advanced‐stage disease. No difference was noted between those treated with surgery, radiation, or both. Statistically significant poor prognosticators included black race (hazard ratio [HR], 2.3961; 95% confidence interval [CI], 1.54–3.72; p = .0001) and stage IIIE/IV (HR, 2.3677; 95%CI, 1.36–4.11; p = .0022). Conclusion Early‐stage salivary gland MALT lymphoma disease may be amenable to unimodality treatment. Even patients with advanced disease have relatively high survivals. © 2014 Wiley Periodicals, Inc. Head Neck37: 18–22, 2015